A systematic review on nurses training in South Africa and its relevance during a pandemic - Mookrey, Naadira (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
This is a systematic review on the training and profession of nurses in South Africa. The researcher used an inductive thematic analysis to explore the themes that emerged from the literature. This review used peer-reviewed articles from Google Scholar, PubMed, Sabinet and EBSCOhost and identified 17 articles that were relevant for the study between the timeframe of 1994-2020. The review was done using Braun and Clarke's thematic analysis and 5 themes were found: Nursing Crisis; Challenges in Nursing; Training Gap; Transformation in Nursing and the Job Profile of Nurses. The study recommended that more research needs to be conducted in certain areas, for example in the Eastern Cape, and to provide better incentives to nurses for example, certificates upon completion of in-service training.
Keywords: Psychology -- South Africa; Nursing -- Study and teaching -- South Africa; Nurses -- In-service training -- South Africa; Nurses -- Supply and demand -- South Africa; Nurses -- Job stress -- South Africa; Health care reform -- South Africa; Medical personnel -- South Africa; Medical education -- South Africa; Systematic review